Suppression of tunnel spalling by engineered rock mass damage - McDonald, AC; McKinnon, SD (Ground Support 2019: Proceedings of the Ninth International Symposium on Ground Support in Mining and Underground Construction, 2019)
Near excavation boundaries in massive to moderately-jointed rock masses, rock predominately fails by extensional fracturing leading to the progressive formation of thin slabs of rock—referred to as spalls. These spalls can buckle, rotate, dilate and accumulate to cause bulking of the rock mass. Spalling can lead to overbreak, ground support damage and capacity consumption by bulking, and ejection of rock (strainbursting). Reliable design of deep excavations depends on reliable forecasts, which require informed understanding of the mechanisms of brittle failure and behaviour. Confinement has been used as a strategy to suppress spalling but this is not always possible. Alternatively, spalling can be suppressed by the accumulation of damage (whether engineered or naturally occurring) to the rock mass. Through an analogue model of a brittle rock mass, we show that engineering damage into the rock mass supresses and can theoretically prevent the occurrence of spalling around an underground excavation. Furthermore, we show that the bimodular ratio, related to the modulus of the intact rock in compressional versus extensional loading, is an important indicator of damage and proneness to strainbursting.
Keywords: spalling